Investigation on the Effect of Atmosphere on the Pyrolysis Behavior and Oil Quality of Jimusar Oil Shale - Zhiqin Kang; Zhijing Wang; Yang Lu; Ran Cao; Dongwei Huang; Qiaorong Meng (Geofluids)
High-temperature H2O and CO2 can improve the pyrolysis behavior of oil shale. Therefore, in this paper, Jimusar oil shale was selected as the research object and the effect of the reaction atmosphere (H2O, CO2, and N2) on its pyrolysis behavior, pyrolysate distribution, and pyrolysis oil quality was fully compared and studied. The results showed that compared with the N2 atmosphere, the presence of H2O and CO2 both increased the weight loss and weight loss rate during pyrolysis of oil shale and the existence of H2O advanced the initial precipitation temperature of volatiles by 17°C. The comprehensive release characteristic indices of volatiles during pyrolysis of oil shale in the CO2 and H2O atmospheres increased by 49.34% and 114.35%, respectively, which significantly improved its pyrolysis reactivity. Both H2O and CO2 atmospheres improved the pyrolysis oil yield of oil shale, and the pyrolysis oil yield in the H2O atmosphere performed better than that in the CO2 atmosphere. Especially, the H2O atmosphere could increase the pyrolysis oil yield by 41.42%. The existence of CO2 prevented methyl radicals from accepting hydrogen radicals during pyrolysis and reduced the alkane yield, while CO2 participated in the addition reaction of alkane, which increased the alkene yield. High-temperature H2O provided more hydrogen source, which increased the alkane yield and inhibited the alkene formation. Both H2O and CO2 atmospheres promoted the cracking of polycyclic aromatics and increased the yield of small-molecular aromatics in the pyrolysis oil. During the pyrolysis process of oil shale, CO2 and H2O underwent reforming reaction with the heavy oil, which increased the light component fraction, thereby increasing the H/C ratio of pyrolysis oil. Thus, the existence of H2O and CO2 atmospheres improved the quality of pyrolysis oil and the effect of H2O was better than CO2. The H2O and CO2 atmosphere promoted the formation of a well-developed pore structure, which was conducive to mass and heat transfer during pyrolysis of oil shale.